The Case of the Missing Fair Use: A Multilingual History & Analysis of Twitter’s Policy Documentation - Johnson, Amy (AoIR Selected Papers of Internet Research, 2016)
This paper traces the history of Twitter’s policy documentation, across languages and time. Drawing on STS scholarship, legal studies, and the growing field of corporate language policy and planning, I examine the language hierarchies—and the social and political assumptions they carry—embedded in Twitter’s policy documentation. I focus particularly on Twitter’s fair use and parody policies and their various iterations. Many of the languages Twitter offers include only minimal documentation—thus, for example, in Suomi, Swedish, and Vietnamese only the Twitter Rules document exists. The fair use document, however, is missing even from those languages that have extensive, otherwise comprehensive coverage. The plight of fair use documentation contrasts sharply with that of the parody policy. Twitter’s parody policy—and in US law parody is not only a matter for freedom of speech doctrine, but is famed as a fair use exception category—appears across 10 of the available languages of Twitter’s policy documentation, roughly 1/3. So why does fair use languish linguistically? Or, what makes the parody policy so special? To answer these questions, this paper draws on a multilingual archive of Twitter’s documentation and accounts of formative exchanges that predate Twitter; interviews with Twitter employees in San Francisco, Tokyo, and Dubai; participant observation at Twitter offices; and a historical corpus of media articles in English, Japanese, and Arabic that offer local contextualization of the changes in Twitter’s documentation.